NEW TECHNOLOGIES AND DATA OWNERSHIP: WEARABLES AND THE EROSION OF PERSONALITY RIGHTS - Kauffman, Marcos E.; Soares, Marcelo Negri (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
<span style="font-size: 12.0pt; line-height: 115%; font-family: ’Cambria’,’serif’; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Arial; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;" lang="EN-GB">As technology continues to evolve at an exponentially increasing pace, it transforms our lives and societies, thus shaping our perceptions of reality with high velocity and impacting the relationship between the individual, the society, and the legal system. The young area of law known as IT Law is attempting to explore the effects of new technologies in our relationships with the law, as well as, identify the best use new technologies to reduce the gap between new technology, new societal behaviours and various legal systems. Therefore, this article aims to make a contribution to the debate by introducing and describing the current use cases of wearable technology in Europe, legal issues that have been exacerbated by these emerging technologies. The article concludes that in order to mitigate the risk of erosion of personality rights new technology and innovation must to be integral components of the legal system in the future.<!–[if gte mso 9]> Normal 0 21 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>